Translation invariant tensor product states in a finite lattice system - 蔡建伟 陈巧妮 赵汇海 谢志远 秦明普 魏忠超 向涛 (Chinese physics B, 2011)
We show that the matrix （or more generally tensor） product states in a finite translation invariant system can be accurately constructed from a same set of local matrices （or tensors） that are determined from an infinite lattice system in one or higher dimensions. This provides an efficient approach for studying translation invariant tensor product states in finite lattice systems. Two methods are introduced to determine the size-independent local tensors.